PENGARUH FITUR ROBO ADVISOR, FOMO, DAN LINGKUNGAN PERTEMANAN TERHADAP MINAT INVESTASI REKSA DANA BIBIT PADA GEN Z DI DKI JAKARTA - Fajriah, Garnis; Silvia, Ani; Maharani, Novita Kusuma (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2025)
ABSTRACTThis research aims to determine the influence of the robo advisor feature, FOMO, and friendship environment on investment interest in Bibit mutual funds among generation Z in DKI Jakarta. A quantitative approach was used in this research, with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique. Data was collected through an online questionnaire distributed to respondents aged 17-27 years who live in DKI Jakarta and have experience using the Bibit application. Of the 265 respondents who participated, 251 valid responses were analyzed using SmartPLS software version 4.1.0.9. The research results show that the robo advisor feature, FOMO, and friendship environment partially have a positive and significant influence on investment interest in Bibit mutual funds among Gen Z. This allows for the importance of ease of investment, fear of being left behind by trends, and the influence of the social environment in increasing investment interest.Keywords: Investment Interest, Robo Advisor Feature, FOMO, Friendship Environment